(untitled) (The Conference Hub, 2025)
This article analyzes the impact of AI-integrated virtual learning platforms on the teaching and learning process of inorganic chemistry. The study explores how the use of artificial intelligence and virtual learning environments enhances students’ knowledge, skills, and competencies in chemistry, fostering independent thinking and scientific analysis abilities. The effectiveness of AI-based virtual laboratories, interactive exercises, and intelligent testing systems is theoretically substantiated. Research findings show that AI integration significantly improves the effectiveness of inorganic chemistry education and serves as a key factor in enhancing the overall quality of learning.